The Effect of Corporate Governance Implementation and Corporate Social Responsibility Disclosure on Firm Value: An Empirical Study on Manufacturing Sector Companies Listed on the Indonesia Stock Exchange in 2022–2023 - Das, Nidia Anggreni; Wahyuni, Lili; Fitri, Rahma; Humaira, Dian; Medinah, Khairatul; Wenda, Marsha Syaidina; Salora, Wiranda (International Journal of Research in Community Services, 2025)
This study aims to analyze the effect of Corporate Governance implementation and Corporate Social Responsibility (CSR) disclosure on company value in manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2023 period. Corporate Governance is measured using several indicators such as institutional ownership and the proportion of independent commissioners. Meanwhile, CSR disclosure is analyzed based on the GRI (Global Reporting Initiative) disclosure index. Company value is measured using the Tobin's Q ratio. This study uses a quantitative method with a multiple linear regression approach. The sample was selected using a purposive sampling technique, with 33 companies meeting the criteria. Data were obtained through annual reports and sustainability reports published by each company. The results of the study indicate that the implementation of Corporate Governance partially has a significant effect on company value, especially on the variables of institutional ownership and independent commissioners. Meanwhile, CSR disclosure is also proven to have a positive and significant effect on company value. Simultaneously, Corporate Governance and CSR disclosure have a significant effect on increasing company value. This study provides implications that companies need to improve the quality of governance and disclosure of social and environmental information to increase investor confidence and company value in the capital market.